Undervisning i jødedommen i Danmark. Kristendom på barnestadiet eller myndigt individ? - Christensen, Merete (Nordisk judaistik, 1986)
Judaism is taught in Danish schools when religious instruction is given, but usually only as an introduction enabling pupils to understand Christianity. Although religious instruction is given throughout the period of nine, eleven or twelve years that most pupils spend in the Danish school system it is not certain that they hear about Judaism as a modern, living religion because pupils and teachers may choose to study other religions instead, such as Islam. Judaism is considered as a stage everybody should have left behind on the way to becoming Christian - rather a childhood stage one should have passed prior to the year 70 A.D. In recent years textbooks have undergone a very positive change, and the preaching element of religious instruction is declining, but the teachers still suffer from the prejudices implanted by their universities or training colleges.